2018
DOI: 10.1242/jeb.171959
|View full text |Cite
|
Sign up to set email alerts
|

Variation in hearing within a wild population of beluga whales (Delphinapterus leucas)

Abstract: Documenting hearing abilities is vital to understanding a species' acoustic ecology and for predicting the impacts of increasing anthropogenic noise. Cetaceans use sound for essential biological functions such as foraging, navigation and communication; hearing is considered to be their primary sensory modality. Yet, we know little regarding the hearing of most, if not all, cetacean populations, which limits our understanding of their sensory ecology, population level variability and the potential impacts of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…(e.g. Mooney et al, 2018;Norman et al, 2012) to assess how hearing abilities may be associated with certain habitats, individual condition, relatedness and chronic stress. By combining hearing data with the acoustic environment around the birds and the frequency content and intensity of their communication sounds, we can address how changes in background noise levels may lead to masking and shorter communication ranges.…”
Section: Resultsmentioning
confidence: 99%
“…(e.g. Mooney et al, 2018;Norman et al, 2012) to assess how hearing abilities may be associated with certain habitats, individual condition, relatedness and chronic stress. By combining hearing data with the acoustic environment around the birds and the frequency content and intensity of their communication sounds, we can address how changes in background noise levels may lead to masking and shorter communication ranges.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, ABRs from both ears from Qila had smaller amplitude, with increased latencies of the dominant waves. (b) Auditory evoked potential audiograms measured in Aurora (left ear, blue circle) and Qila (left ear, red closed squares; right ear, red open squares), in comparison with those reported by Mooney et al ( 25 ) for 26 belugas. Underwater ambient noise levels (power spectral density, units of 1 μPa 2 /Hz) for the pool in which Aurora and Qila were tested are shown with a dotted line.…”
Section: Methodsmentioning
confidence: 82%
“…Following click-evoked ABR testing, hearing thresholds as a function of frequency (AEP audiograms) were measured for both belugas. The thresholds for Aurora, Qila, and 26 wild belugas previously tested using similar AEP methods ( 25 ) are shown in Figure 1b . This large sample size from Mooney et al ( 25 ) bounds nearly all other AEP thresholds reported for belugas ( 17 , 26 , 27 ), and thus they are used to provide a reference to the normal values for this species and method [but see ( 28 – 32 ) for behavioral thresholds].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations